Response Surface Analysis of Cold Formability of Polymers in Incremental Sheet Forming: Effect of Parameters and Associated Thermal Softening - Hussain, Ghulam; Mahna, Aminreza; Iqbal, Asif (Korean Soc Precision Eng, 2016)
The response surface approach was employed to analyze the influence of process parameters and associated thermal softening on the cold formability of two polymers, namely PVC and PE, in ISF. Three process parameters namely r/to, r/p and. omega/f were varied over wide ranges. To know the effect of temperature variations on the ductility of material, thermal softening index was defined as Delta T/mp (Delta T is rise in temperature and mp is melting point of material). The magnitude of this index increased with the increase in the value of considered parameters. Further, for given set of parameters, its value was low for PVC and high for PE. Regarding its influence on forming, it was observed to significantly affect the formability and type of failure. For PVC, the formability increased with an increase in its value; however, for PE, the formability contrarily reduced. Moreover, the failure in the former material (low index and high strength) occurred due to fracture and in the latter (high index and low strength) took place due to wrinkling. These findings led to conclude to attain low softening index for maximizing the formability of soft polymers (say PE) and high index for the high strength polymers (say PVC).
Keywords: Formability; ISF; Softening; Model; Optimization; Polymer